From Intention to Action: The Role of Conscious and Subconscious Minds in Personal Transformation - Muhammad Owais Isaac (HISTORICAL: Journal of History and Social Sciences, 2024)
This paper explores the relationship between the conscious and subconscious mind, focusing on how this interplay influences human behaviour and character development. Drawing on the teachings of the Quran, it examines the concept of free will and the responsibility individuals have for their choices. The study highlights how conscious actions shape subconscious habits, emphasizing that repeated behaviours can lead to automatic responses that reflect one’s character. The Quran underscores the importance of personal accountability and the potential for self-transformation through intentional actions. By aligning subconscious tendencies with conscious intentions, individuals can cultivate positive traits and move closer to their spiritual goals. This research offers insights into the dynamics of human behaviour and the spiritual implications of our choices, guided by the principles found in the Quran. It also explores the dynamics between the conscious and subconscious mind, emphasizing the notion that the subconscious mind predominantly governs our daily activities. It posits that while the conscious mind is primarily engaged in new learning processes, the subconscious mind, shaped by both inherent traits and conscious learning, automates routine tasks and influences decision-making through.